The UFO Abduction Syndrome - Donderi, Don C.; Davis, Ted; Hopkins, Budd (Journal of Scientific Exploration, 2013)
<!--[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif] --> Some people say that they have been abducted by extraterrestrials. We obtained responses to 608 true–false questions from 52 self-reported abductees and compared their responses to those of 75 non-abductee controls and to 26 simulators whom we asked to respond “as if” they had been abducted. The entire question set, as well as a subset of 65 questions identified by discriminant analysis, differentiated among self-reported abductees, controls, and simulators. This result helps to define a state of mind that we call the UFO Abduction Syndrome.